Supervivencia y crecimiento de plantulas de caoba en aperturas creadas en la Selva Maya de Belice y Mexico - Snook.L.K.=700 1 Negreros Castillo, P.; O'Connor, J.
(En, Es)
ilus., 20 ref.
Keywords: SWIETENIA MACROPHYLLA; REGENERACION; CRECIMIENTO; SILVICULTURA; HYPSIPYLA GRANDELLA; INSECTA; PLANTACION; BELICE; AMERICA CENTRAL; MEXICO; CAOBA